Social Media Advertising on Customer Purchasing Decisions - Princeska Marsha Setiabudi; Teresa Avilla Valentine Saputra; Keisha Aurelia Rianto; Juliana Juliana; Amelda Pramezwary (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
Advertising on social media is a place where sellers can offer their products through online media· The distribution of advertising on social media can influence the decision to purchase a product, especially when sales experience a decline· This research aims to determine the effect of advertising via social media on customer purchasing decisions at Starbucks· This research method uses a questionnaire survey and data analysis using SmartPLS4· The research sample consisted of 100 Starbucks customer respondents· The sampling technique uses convenience sampling· The research results show that advertising via social media influences customer purchasing decisions at Starbucks· Advertising via social media can increase brand awareness and improve customer purchasing decisions· The results of this research can help Starbucks improve its marketing strategy through social media to increase sales and customer satisfaction· The results of this research can help companies like Starbucks strengthen their marketing strategies via social media to increase sales and customer satisfaction· Advertising via social media can be used to increase brand awareness and improve customer purchasing decisions· Future research could add additional variables such as service quality, price, and location to further understand how advertising via social media influences customer purchasing decisions.